Experiencias del personal de salud con el uso de hidratación paliativa en pacientes con demencia avanzada - Corzo Camacho, Mario Alberto (Universidad Antonio Nariño, 2023)
Introduction: Dementia is a life-changing disease that often causes dysphagia. Although some clinicians consider artificial hydration part of treatment, evidence rejects its effectiveness. This scenario creates challenges and dilemmas for health personnel, family members, and caregivers